2017
DOI: 10.1044/2017_jslhr-s-16-0096
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Attentional Set-Shifting and Inhibition in Children Who Stutter

Abstract: The findings on error percentages partly corroborate earlier questionnaire-based findings showing difficulties in CWS on AS and IC. Moreover, it also seems to imply that CWS are less able to slow down their responses to achieve higher accuracy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 95 publications
1
28
0
1
Order By: Relevance
“…The Covert Repair Hypothesis proposes that disfluencies are the product of covert detection and corrections of prearticulatory errors which interfere with ongoing articulation, and higher rates of disfluencies are due to multiple or excessive attempts at repairs [ 13 ]. First, weaker attention control as reported in CWS [e.g., 9 , 10 , 113 , 114 ] may result in excessive attention on prearticulatory errors or an inability to shift attention away from repaired segments, whereby, numerous repair attempts are made, contributing to high rates of disfluencies. Second, weaker inhibitory control would also prevent suppression of excessive corrections of speech plans, yielding high rates of disfluencies [ 127 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Covert Repair Hypothesis proposes that disfluencies are the product of covert detection and corrections of prearticulatory errors which interfere with ongoing articulation, and higher rates of disfluencies are due to multiple or excessive attempts at repairs [ 13 ]. First, weaker attention control as reported in CWS [e.g., 9 , 10 , 113 , 114 ] may result in excessive attention on prearticulatory errors or an inability to shift attention away from repaired segments, whereby, numerous repair attempts are made, contributing to high rates of disfluencies. Second, weaker inhibitory control would also prevent suppression of excessive corrections of speech plans, yielding high rates of disfluencies [ 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been growing interest in the development of inhibitory control in CWS but findings have been contradictory [for a review see 6 ]. Some studies using direct measures of inhibition (e.g., Go/NoGo tasks) report lower accuracy and slower reaction time in preschool- and school-age CWS compared to CWNS [ 9 , 10 , 113 , 114 ]. However, others have failed to find differences (e.g., in the number of correct inhibitions) between CWS and CWNS using similar tasks [ 115 ].…”
Section: Introductionmentioning
confidence: 99%
“…In examining the characteristics of these studies, we observe that all but two studies examined simple response inhibition and that the findings from the two studies that examined complex response inhibition 30,35 were mixed. Findings based on sample sizes also varied; while two of the studies that reported differences had the largest sample sizes (30 or more participants), some studies employing smaller sample sizes also found differences.…”
Section: The Inhibition Skills Of Cwsmentioning
confidence: 99%
“…Nonword repetition tasks require at least sustained attention to speech sounds over a number of trials, the capacity to hold the speech sounds for up to a few seconds, and then to accurately execute the sequence in the order it was presented. Further, both CWS and AWS present with subtle differences in a number of cognitive capacities that could affect behavioral performance on a nonword repetition task, including attention/executive function (Postma and Kolk, 1993;Alm, 2004;Eggers et al, 2012Eggers et al, , 2013Eggers and Jansson-Verkasalo, 2017), phonological encoding (Postma and Kolk, 1993), speech planning (Howell and Au-Yeung, 2002), speech-sound processing (Neef et al, 2012;Saltuklaroglu et al, 2017), and differences in speech-motor control for execution interacting with cognitive and emotional factors (Namasivayam and van Lieshout, 2011;Smith and Weber, 2017). In addition, it is also unclear how factors such as working memory load (e.g., number of syllables) contribute to observed differences in previous studies (Pelczarski and Yaruss, 2016).…”
Section: Phonological Working Memory Background and Need For Preliminmentioning
confidence: 99%
“…Given the functional overlap, it perhaps does not seem surprising that the effects of stuttering can transcend speech production and impact cognitive function. Thus, the growing behavioral evidence of these cognitive effects in PWS (Byrd et al, 2015;Eggers and Jansson-Verkasalo, 2017;Eichorn et al, 2018;Coalson et al, 2019), make it necessary to understand their neural correlates. An added advantage of studying the effects of stuttering on cognitive function is that it can provide a valuable window into understanding how sensorimotor function differs in PWS without the potentially contaminating effects of overt stuttering.…”
Section: Introductionmentioning
confidence: 99%